On a complete set of functions associated with a peculiar eigenvalue problem - López, A. (Instituto de Física "Dr. José A. Balseiro". Universidad Nacional de Cuyo, 1972)
Fil: López, A. Comisión Nacional de Energía Atómica; Argentina